Sun-Protective Clothing Design for Wheelchair Users: Integrating Function and Accessibility (Journal of Fiber Bioengineering and Informatics, 2025)
Research on sun-protective clothing for wheelchair users is of great significance in advancing the development of accessible clothing. Currently, sun-protective clothing available on the market is mainly designed for the general public. Traditional sun-protective clothing has shortcomings in multiple aspects such as garment length and bottom hem circumference, failing to meet the daily wearing needs of wheelchair users. Based on this, this study aims to design sun-protective clothing that caters to the needs of wheelchair users. The study employed questionnaire surveys and interviews, identifying seven key design points, and proposed a systematic design method based on three functional areas: sun protection, breathability, and safety protection. In the sun protection functional area, the sun protection area is determined by integrating the characteristics of the fabric and the wearing scenario. In the breathable functional area, the breathable area is determined and suitable materials are screened. In the safety protection functional area, reflective materials are integrated into the clothing structure line. Based on this, this study designs barrier-free settings for sun protection clothing. Three testers were invited to conduct wear testing and evaluation. The results showed that the comfort and functionality of the sun-protective clothing have been significantly improved, providing new design ideas for accessible clothing and creating possibilities for wheelchair users to have more suitable sun-protective clothing in the summer.
Keywords: Sitting sun-protective clothing; Wheelchair users; Accessibility design; Parking Demand Study